Truancy Behavior in terms of the cause at SMP 13 Padang - Ope Yulia Regina; Marjohan Marjohan (Jurnal Neo Konseling, 2021)
Truancy behavior is a form of undiscipline or student violation of school rules of conduct which will harm themselves and others such as leaving behind subject matter.In today's world, the phenomenon of truancy that occurs in the field is abundant. Based on observations and interviews that have been conducted with the school and the students themselves, truancy behavior is based on two factors, namely internal factors such as physical and psychological conditions, the second is external factors such as family and economy, society, and school. Therefore, the problem that will be examined in this research is, "Truancy Behavior in terms of Causative Factors at SMPN 13 Padang". This type of research is a descriptive study using quantitative methods. The subjects in this study were 40 students of class VIII and IX 2020/2021 SMPN 13 Padang, subject taking was done by selecting respondents who were sampled based on certain characteristics. Collecting data using a questionnaire about truancy behavior in terms of the factors that cause students in class VIII and IX at SMPN 13 Padang Likert scale model. The results showed that: Internal factors, namely (1) Physical conditions affect students not to come to school. (2) Psychological conditions influence students not to come to school. External factors, namely (1) family and economic conditions ((a) Family conditions influence students not to come to school. (b) Economic conditions affect students not to come to school). (2) Community conditions influence students not to come to school. (3) School conditions influence students not to come to school. Based on the findings of this study, it is hoped that counseling teachers can provide counseling guidance services in accordance with the problems faced by students to minimize truancy.